Unique continuation for fractional Schrödinger equations with rough potential - Rüland, Angkana (Arxiv, 2013)
This article deals with the weak and strong unique continuation principle for fractional Schr\"odinger equations with scaling-critical and rough potentials via Carleman estimates. Our methods allow to apply the results to variable coefficient versions of fractional Schr\"odinger equations.